Analysis of the Influence of Online Shopping Consumption Through E-commerce Shopee Among Students of the Faculty of Economics UIN Malang - Rohmah, Nur Halizah Aulia; Retnasih, Nora Ria (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This analysis aims to evaluate the consumerist influence of online shopping through the Shopee e-commerce platform on students of the Faculty of Economics at UIN Malang. This research aims to understand the extent of consumer tendencies and their impact on the financial behavior of students at the Faculty of Economics, UIN Malang. The research method used is a questionnaire or survey, with a target sample representing students of the Faculty of Economics at UIN Malang for the academic years 2019-2022. The research results show a significant influence of online shopping consumption through Shopee on students of the Faculty of Economics at UIN Malang. Factors such as ease of access, promotional offers, convenience, product variety, and social influence play an important role in driving consumer behavior. However, it is important to remember that such consumerism can have negative financial consequences if not managed properly, which can lead to financial difficulties in the future.